Eye hydrodynamics indicators in children with congenital cataract, aphakia and pseudophakia - L. S. Khamraeva; L. Yu. Bobokha; L. A. Katargina (Российский офтальмологический журнал)
Purpose. To determine the specificity of functional and tonographic parameters of the eyeball in children with cataract, aphakia and pseudophakia. Material and methods. A comparative analysis of eye hydrodynamics indices was made according to a simplified procedure, using the Friedenwald nomogram, on 75 children aged 2 to 17 years with cataract (24 eyes), aphakia (21 eyes), pseudophakia (15 eyes), and IOL dislocation (15 eyes), as well as 12 healthy children.Results. In pseudophakia, true IOP was found to fall to 10.00 ± 0.01 mm Hg due to a decrease in aqueous humor production (to 0.10±0.01 mm3 / min) and increase of its outflow (to 0.75 ± 0.02 mm3/min / mm). IOL dislocation led to an increase in true IOP (24.40±1.0 mm Hg) due to an increase in aqueous humor production (4.09±0.05 mm3/min) and a decrease in its outflow (0.010 ± 0.002 mm3/min/mm). In these eyes, clinical manifestations of secondary pseudophakic glaucoma were noted, which are explained by factors obstructing aqueous humor outflow (vitreous prolapse and partial vitreous block) and considered an indication for re-operation.Conclusion. Statistically significant changes of hydrodynamic eye parameters in children with pseudophakia have been detected: increased true IOP in IOL dislocation, and, conversely, reduced true IOP in case of the normal IOL location. The authors believe that eye “hypotension” in case of pseudophakia requires further study.